Role of journalists' gender, work experience and education in ethical decision making - Motlagh, Nafise E.; Hassan, Md. Salleh; Bolong, Jusang; Osman, Mohd Nizam (Canadian Center of Science and Education, 2013)
This research was conducted to determine the role of journalists’ gender, work experience and education in their ethical decisions in uncertain situations. The instrument used was structured and self-administered questionnaire. This quantitative descriptive study selected 231 full-time Malaysian journalists from five highly-circulated newspapers in April 2011. Non-probability sampling (convenience) was applied to collect the data and to estimate the characteristics of the whole population. The results showed that more than half (51.8%) of the 228 journalists made unfair decisions about seven short presumptive statuses, which were designed based on the Malaysia National Union of Journalists’ codes of ethics. According to this study, neither gender nor journalism education made any difference in journalists’ ethical decisions. The findings also showed the more work experience the journalists had, the more fair decisions they made in uncertain situations.